Postantibiotic Effects of Garenoxacin (BMS-284756) against 12 Gram-Positive or -Negative Organisms - Pankuch, G. A. (American Society for Microbiology, 2003)
Conventional in vitro methods were used to determine the postantibiotic effects (PAEs), sub-MIC effects (SMEs), and postantibiotic sub-MIC effects (PA-SMEs) of garenoxacin for a range of organisms. The mean PAEs of garenoxacin for pneumococci, staphylococci, and enterococci were 0.3 to 2.2 h. For Escherichia coli and Pseudomonas aeruginosa, the PAEs were 0.9 to 1.6 h. The mean PA-SMEs (0.4 times the MIC) for pneumococci, staphylococci, and enterococci were 3.0 to >10 h, 1.8 to >10.7 h, and 5.8 h, respectively, while those for E. coli and P. aeruginosa were 7.6 and 4.4 h, respectively.